Implikasies van 'n postmodernistiese lees van die Ou Testament vir die terreine van die teologie, die bybelwetenskap, die publiek en die kerk - JPH Wessels (Acta Theologica)
Traditionally textual analysis of the Old Testament is done within a modernist framework. However, a postmodernist approach opens up new avenues in this regard. The reading strategy of critical deconstruction, based on the premise chat meaning in a cext is not fixed but is rather something elusive of which only traces can be found in a text, creates exciting possibilities for the reading of the Hebrew Bible. This reading strategy has implications when applied to the Bible. Besides the implications for textual meaning, this approach also has implications for biblical science, the public and the church.